Pemberdayaan kelompok petani tambak ikan kakap putih (Lates calcarifer, Bloch) dengan menggunakan teknologi secara modular di Gampong Lancang Barat Kabupaten Aceh Utara (Empowerment of sea bass farmers group (Lates calcarifer) using modular technology in Lancang Barat Village, North Aceh District) - Ayuzar, Eva; muliani, muliani; Khalil, Munawwar; Zuriani, Z; Hatta, Muhammad; Adhar, Saiful (Buletin Pengabdian, 2022)
The purpose of this service activity is to increase the knowledge regarding white snapper cultivation using modular technology to the aquaculture farmer group in West Lancang Village, North Aceh District. This service activity used a survey, educative, participatory, and persuasive methods. This community service activity consists of several stages, namely: 1) counseling on white snapper cultivation techniques carried out in a modular manner starting from nursery to harvest 2) counseling on business analysis of white snapper, and 3) training on pond water quality measurement methods. The level of success and satisfaction of service participants was carried out using a questionnaire. Based on the analysis of the level of satisfaction and success, 80-90% of pond farmers are satisfied with this service activity. This service activity provides positive knowledge and motivation for pond farmers. In conclusion, this empowerment activity has a positive impact and increases the knowledge of pond farmers in cultivating white snappers with modular technology.